Moderating effect of organizational culture on the relationship between workplace learning and job performance in selected public organizations in Malaysia - Daryoush, Younes (2014)
The purpose of this study was to investigate the moderating effect of organizational culture on the relationship between workplace learning and job performance in the Malaysian public sector. The conceptual model proposed that workplace learning was assumed to associate with job performance, and this association is influenced by organizational culture. In this respect, relationships were examined among three types of workplace learning (formal, informal, and incidental), five types of organizational culture (result orientation, innovation orientation, teamwork orientation, communication orientation, employee orientation), and two types of job performance (task performance, contextual performance). The subjects of this study were Malaysian officers who had worked in the public sector more than one year, and agreed to complete the survey. A questionnaire with 64 questions (excluding demographic items) was designed. About 369 hundred questionnaires were distributed to two organizations, and 338 responses were collected. The final response rate, after 16 unusable responses were identified, was 95% (322). Cronbach’s alpha verified the reliability of the overall instrument, as well as the sections of the survey. Construct validity was determined using confirmatory factor analysis (CFA). Correlation analysis and structural equation modelling (SEM) techniques by Amos 18 were conducted to test the hypotheses of the study. The results showed a significant positive relationship between workplace learning (formal, informal and incidental) and job performance (task and contextual).The current research also found a significant positive relationship between result orientation culture with two types of job performance but there was a significant relationship between employee orientation culture and task performance. In addition, the moderating effect of innovation, teamwork, communication, and employee orientation culture on the relationship between informal workplace learning and job performance (task and contextual) were significant. Moreover, the moderating effect of innovation, and employee orientation culture on the relationship between incidental workplace learning and contextual performance were significant. The results of this study provide an insight and add new knowledge to a public sector environment which can help increase formal and informal workplace learning among employees, as this can facilitate positive workplace behaviours and strengthen organizational performance. Strategies such as workplace interventions, in-service training techniques may increase levels of contextual performance and task performance from moderate to high. Based on the results of the study, several issues are discussed. Additionally, research directions for future research are recommended, and both theoretical and practical implications for Human Resource Development are provided.